Pengujian Peluahan Sebagian Menggunakan Rogowski Coil Inti Ferit dan Non Ferit dengan Variaasi Lilitan Sebanyak 10 Lilitan - Lestari, Asri Indah; Fadilah, Fadilah; Fadilah (JURNAL SURYA ENERGY, 2022)
Partial Discharge is one of the phenomena that occurs in the electric power system, which is characterized by the phenomenon of heat which will disrupt the insulation system. If this phenomenon is left for a long time, it will disrupt the process of distributing electricity, even stopping the process of distributing electricity. Partial discharge testing can be tested in 2 ways, namely conventional using coupling and conventional using electromagnetic methods, optical methods, acoustic methods, and chemical methods. Moisture testing in part in this study uses a non-conventional method with the electromagnetic method. The electromagnetic method used is the Rogowski Coil with ferrite and non-ferrite cores. Each Rogowski Coil core has an inner diameter of 1.2 cm, an outer diameter of 2.5 cm, a height of 2.5 cm and a total of 10 turns. The results of the partial sweat test show that the non-ferrite core Rogowski Coil responds faster than the ferrite core Rogowski Coil. As for the sensitivity level of the second core used for partial discharge testing, it can be seen that the Rogowski Coil with a ferrite core is more sensitive than the non-ferrite core with a sensitivity value of 11.63%.